A SMART CITY APPLICATION VALUE PROPOSITION REALITY CHECK AND CHALLENGES: THE CASE OF MOBILE APPLICATION FOR LOCAL TAX INFORMATION AND PAYMENT - Sanawiri, Brillyanes; Agusti, Rosalita Rachma (The International Journal of Accounting and Business Society, 2019)
This paper address the problem and challenges of the smart city application in the field of tax service. The smart city application for local tax information and payment or namely the SAMPADE App is an innovative service provided by the city government of Malang, Indonesia. The four elements of value proposition and seven smart city framework dimensions were employed to evaluate the Smart City app of SAMPADE. A qualitative study was used by interviewing users and stakeholders of the mobile application. The study indicate that all four elements of the value proposition were currently perceived useful, however improving the performance and reliability of the apps requires further developments. The main contribution of this paper is the qualitative dimension of the concept of the value proposition and the smart city framework used to evaluate the smart city app. Future challenges and recommendation are also presented in this paper as part of the broader exercise for policymakers in developing the smart city app for local tax information and payment.Keywords: Value Proposition, Smart City, Local Tax, E-Government